Unreal Engine 4: Realtime Motion Graphics. - Pagano, Scott (linkedin.com, 2016)
Speed up your workflow by leveraging the real-time processing power of Unreal Engine 4. Find out how to take static and animated geometry from Maya and C4D and render it in Unreal.